Cancer-associated fibroblasts mediate resistance to anti-EGFR therapies in cancer - Shuang Dai; Yingtong Liu; Zheran Liu; Ruidan Li; Feng Luo; Yan Li; Lei Dai; Xingchen Peng (Elsevier, 2024)
Over the last decade, epidermal growth factor receptor (EGFR)-targeted therapies have transformed the treatment landscape for patients with advanced solid tumors. Despite these advances, resistance to anti-EGFR therapies is still a significant clinical challenge. While cell-autonomous mechanisms of resistance are well-documented, they do not fully elucidate the complexity of drug resistance. Cancer-associated fibroblasts (CAFs), key mediators within the tumor microenvironment (TME), have emerged as pivotal players in cancer progression and chemoresistance. Recent evidence implicates CAFs in resistance to anti-EGFR therapies, suggesting they may undermine treatment efficacy. This review synthesizes current data, highlighting the critical role of CAFs in resistance pathogenesis and summarizing recent therapeutic strategies targeting CAFs. We underscore the challenges and advocate for the exploration of CAFs as a potential dual-targeted approach.